Smearing the trundles of legal aid in Cameroon: reconsidering the need in appraising the legal framework - Charles Nguindip, Nana (DIXI, 2025)
The provision of legal aid to indigent defendants in criminal proceedings in Cameroon faces numerous operational and legal challenges. Despite the country’s ratification of key international legal instruments recognizing the need to provide legal aid in criminal cases—particularly for the accused—its policies for incorporating the right to legal aid into domestic legislation and other enabling laws remain problematic. Various oversight deficiencies hinder the effective implementation of public legal aid schemes, particularly in criminal proceedings. As a result, a significant number of accused persons, often unfamiliar with the complexities of the adversarial criminal justice system, are compelled to represent themselves, putting their legal rights at serious risk. This article argues that enhancing the legal aid system and ensuring its sustainability in Cameroon’s criminal justice process can only be achieved through a comprehensive review of the normative framework governing the right to legal aid and its implementation under public legal aid schemes. The article concludes that the legal and regulatory frameworks governing legal aid in Cameroon suffer from serious shortcomings, which have undermined the country’s limited efforts to fulfil its international obligations to provide state-funded counsel to indigent defendants. Additionally, the article contributes to the broader discourse on the promotion of legal aid in Cameroon’s criminal justice system, where existing research has predominantly focused on inadequate funding as the primary cause of its inefficiency.